Manajemen Krisis BK di Era Digital: Analisis Kerangka Digital Triage untuk Prioritas Penanganan Kasus Siswa Berbasis Teori Hierarki Kebutuhan Maslow: Manajemen Krisis BK di Era Digital: Analisis Kerangka Digital Triage untuk Prioritas Penanganan Kasus Siswa Berbasis Teori Hierarki Kebutuhan Maslow - Hanung Sudibyo (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
The surge in mental health crises among students post-pandemic requires a case management system that is fast, accurate, and adaptive to resource constraints. Unfortunately, to date, there is no specific triage protocol for Guidance and Counseling (BK) services that integrates psychosocial parameters with a digital framework. This study aims to develop a digital triage model based on Maslow's Hierarchy of Needs as a framework for classifying the priority of student crisis management. The method used was a Systematic Literature Review (SLR) based on the PRISMA protocol for selected scientific documents and policies (n=25), which were then analyzed using a thematic analysis approach assisted by NVivo 14. The analysis yielded four main themes: urgency indicators, crisis response time, use of digital media (WhatsApp and Google Forms), and Maslow-based need stratification. The developed digital triage system prototype demonstrated high content validity (CVR = 0.82), strong inter-coder reliability (Cohen’s Kappa > 0.80), and 92% classification accuracy in a simulation of 50 cases. This study concludes that integrating psychological theory with simple technology can accelerate decision-making processes in risk-based counseling services and serve as a foundation for national policies aimed at achieving more standardized, adaptive, and data-driven responses to psychosocial crises.